ANNOUNCEMENTS (Journal of Finance, 2025)
AFA Financial and Board Meeting Summaries: The AFA Board of Directors has voted to publish a Board Meeting Summary to increase transparency of AFA governance and decisions made by the Board. Recent Board Meeting Summaries as well as AFA Financial Statements are posted on the AFA website (www.afajof.org). We hope that this additional communication is informative and we welcome your feedback. Other Announcements: Please go to our website, www.afajof.org, for announcements regarding AFA news, meetings, conferences, and research support. Effective with the 2024 volume, members and individual subscribers to the Journal of Finance will begin migrating to online access. This is a proactive move towards reducing the environmental impact caused by the production and distribution of printed journal copies and will allow the journal to invest in further innovation, digital development and sustainability measures. Published articles will continue to be published on Wiley Online Library and disseminated quickly through the journal's broad network of indexing services. Articles will also continue to be discoverable through popular search engines such as Google.